Fatal Retroperitoneal Bleeding Caused by Neurofibromatosis: A Case Report and Review of the Literature - Patrick R. Moerbeek; Jesse M. van Buijtenen; Baukje van den Heuvel; Arjan W. J. Hoksbergen (Case Reports in Medicine)
A young female was brought into the emergency department with pulseless electrical activity (PEA) after local resection of neurofibromateous lesions. Chest ultrasonography was normal. Abdominal ultrasonography was not performed. After successful resuscitation a total body CT-scan was performed to rule out potential bleeding sources. However, haemodynamic instability reoccurred and the scan had to be aborted at the thoracoabdominal level. No thoracic abnormalities were found. Resuscitation was reinitiated and abdominal ultrasonography was performed, showing a large amount of abdominal fluid. A progressive fall in haemoglobin was noted. Emergency laparotomy was performed, revealing a large retroperitoneal haematoma. Despite ligation and packing, bleeding continued. Postoperative angiography showed active bleeding from a branch of the left internal iliac artery, which could be successfully coiled. Unfortunately, the patient died five days later due to irreversible brain damage. Revision of an MRI scan made one year earlier showed a 10 cm large retroperitoneal neurofibromatous lesion exactly at the location of the current bleeding. This case shows that patients with neurofibromatosis might develop spontaneous life-threatening bleeding from retroperitoneal located lesions. Furthermore, it points out the necessity of focused assessment with ultrasonography of the abdomen in all patients with PEA of unknown origin.